The role of energy as a geopolitical factor for the consolidation of Greek-Israeli relations. - Ioannis Mazis; Ioannis Sotiropoulos (Regional Science Inquiry, 2016)
During the current historical coincidence, the geostrategic conjunction of Greece-Cyprus- Israel is a reality, in order for the three states to cope in the best possible manner with the contemporary and future challenges in the arena of international and regional relations. Having a common strategic perception of the geopolitical sub-system of the southeastern Mediterranean, Athens, Nicosia and Jerusalem strengthen day by day their political, diplomatic, economic and military relations, aiming at the preservation of stability in the area, against any revisionist factor. For the aforementioned strategic alliance, the discovery, extraction and exploitation of the hydrocarbon neo-reserves within the Greek, Cypriot and Israeli consecutive Exclusive Economic Zones, (EEZs), is the dynamic catalyst that reinforces even further the allied cooperation and effectiveness. Amidst the geopolitical transformation of the wider region of North Africa, Middle and Near East, the construction of the East Mediterranean Pipeline, (East-Med), is a common pursuit of the outmost significance, for the strategic alliance. Indeed, if the East-Med is realized, it will be able to transfer, in the first phase, the Israeli and Cypriot hydrocarbons from the off-shore neo-reserves via Greek sovereign territory and EEZ to Italy and central Europe, signaling EU’s gradual disengagement from the dependence on the Russian natural gas, allowing the EU to make its first steps of energy emancipation. Despite Ankara’s attempt for rapprochement with Jerusalem, the official Israeli position heavily leans towards an Israel-Greek-Cypriot strategic alignment, as Israel’s national security constitute the ultimate long-term priority for Jerusalem. Above all, such a development will upgrade the geopolitical status of all the three states of the strategic alliance in the regional geopolitical as well as the supra-geopolitical system.